Exploring user satisfaction in digital healthcare: The role of doctor-patient communication, service quality, and user experience on Halodoc's online medical platform (a PLS-SEM Analysis) - Wijaya, Sifa Sahdani; Afifi, Subhan (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2024)
The integration of digital technology into healthcare services, particularly through telemedicine, has greatly improved user convenience and accessibility. This study examines the influence of effective communication and service quality on user satisfaction with the Halodoc application, with user experience evaluated as a potential moderating factor. Adopting a quantitative research approach, data were gathered via an online survey of 184 purposively selected respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that effective communication does not significantly impact user satisfaction directly, whereas service quality has a strong and positive effect. Moreover, user experience independently enhances user satisfaction but does not significantly moderate the relationships between effective communication, service quality, and user satisfaction. This study contributes to the academic field of health communication by providing valuable insights into factors shaping user satisfaction within telemedicine platforms. From a managerial perspective, the results underscore the necessity of ongoing innovation in service delivery. Additionally, they emphasize the importance of enhancing the responsiveness and professional competence of healthcare providers through structured training programs to better meet user needs and expectations.